Sexual behavior among students of a public university - Firmeza, Sílvia Noeli Ramos de Melo; Fernandes, Karla Jéssik Silva de Sousa; Santos, Ellane Nunes dos; Araújo, Wylania Jéssica Gomes de; Oliveira, Ellaine Santana de; Silva, Ana Roberta Vilarouca da (Rev Rene, 2016)
Objective: to analyze the sexual behavior among students and their relation to sex.Methods: an analytical study with 154 students accomplished through a form containing socioeconomic and sexuality issues. Results: most of the participants were female, aged between 18 and 30 years old, and initiated sexual life before 18 years old. Participants reported finding necessary information about sexuality especially in conversations with friends and on the internet and found to have satisfactory knowledge. Conclusion: the student’s present vulnerabilities, such as early onset of sexual practices and barrier with the family dialogue.